Все о саде и огороде в вопросах и ответах - Ганичкина Октябрина Алексеевна (Эксмо, 2009)
Экземпляры: ф.2 (2010) / Инвентарный номер: 53114 / Цена: / Сис.шифр: 42.37 / Авт.знак: Г 19 / ГРНТИ: 68.35 / ББК: 42.37